2016
DOI: 10.1104/pp.16.01227
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of P700 in Photosystem I Is Essential for the Growth of Cyanobacteria

Abstract: The photoinhibition of photosystem I (PSI) is lethal to oxygenic phototrophs. Nevertheless, it is unclear how photodamage occurs or how oxygenic phototrophs prevent it. Here, we provide evidence that keeping P700 (the reaction center chlorophyll in PSI) oxidized protects PSI. Previous studies have suggested that PSI photoinhibition does not occur in the two model cyanobacteria, Synechocystis sp. PCC 6803 and Synechococcus elongatus PCC 7942, when photosynthetic CO 2 fixation was suppressed under low CO 2 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
102
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 46 publications
4
102
0
Order By: Relevance
“…5F). These data suggest that FLV-mediated AEF is required to maintain P700 in an oxidized state under fluctuating light in M. polymorpha, which is similar to observations of the cyanobacterium S. 6803 (Allahverdiyeva et al, 2013;Shimakawa et al, 2016b). ) was turned on at the zero time point.…”
Section: Effects Of Flv On Photosynthetic Parameters In Psii and Psisupporting
confidence: 81%
See 2 more Smart Citations
“…5F). These data suggest that FLV-mediated AEF is required to maintain P700 in an oxidized state under fluctuating light in M. polymorpha, which is similar to observations of the cyanobacterium S. 6803 (Allahverdiyeva et al, 2013;Shimakawa et al, 2016b). ) was turned on at the zero time point.…”
Section: Effects Of Flv On Photosynthetic Parameters In Psii and Psisupporting
confidence: 81%
“…1A). In plant leaves and cyanobacterial cells, photoinhibition of PSI is alleviated by the oxidation of P700, owing to a decrease in the amount of photooxidizable P700 (Sejima et al, 2014;Shimakawa et al, 2016b). These data indicate that FLVmediated AEF contributes to the oxidation of P700 in M. polymorpha.…”
Section: Effects Of Flv On Photosynthetic Parameters In Psii and Psimentioning
confidence: 74%
See 1 more Smart Citation
“…Also, photorespiration can be explained as an O 2 -dependent AEF in the broad sense171819. A large O 2 -dependent AEF that replaces photosynthesis can alleviate photoinhibition by dissipating excess energy to O 2 111213171819202122. Recently, we showed that an O 2 -dependent AEF is essential for the oxidation of P700 under CO 2 limitation to protect PSI against photo-oxidative damage in the cyanobacterium Synechococcus sp.…”
mentioning
confidence: 99%
“…Recently, we showed that an O 2 -dependent AEF is essential for the oxidation of P700 under CO 2 limitation to protect PSI against photo-oxidative damage in the cyanobacterium Synechococcus sp. PCC 7002 (S. 7002)2223. That is, oxygenic phototrophs accessed O 2 to prevent photo-oxidative damage derived from O 2 .…”
mentioning
confidence: 99%